A comparative study on the effectivity of live lectures and video recording in the development of psychomotor skills among dental students - Ang, Angelica Y.; Conanan, Cristhy Marie Socorro C.
Two groups of first and second year students of the University of the Philippines College of Dentistry were given lectures on Origami, a Japanese art of paper folding. One group took the lessons from a vidoe recording while the other had a live lecture. Both lectures were given simultaneously after which tests were given to assess the students' cognitive and psychomotor skills. The results show that the students of the video-recorded lecture presented better cognitive and psychomotor skills compared to the students of the live lecture. It was also found out that students' achievement were not affected by their attitude toward television.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental students -- University of the Philippines; Motor skills